2021
DOI: 10.3390/ijerph18041604
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Moral Education on Pro-Environmental Behaviour: Do Psychological Empowerment and Islamic Religiosity Matter?

Abstract: In light of increasing concerns about global environmental problems, environmental moral education is assumed to have a significant influence on the pro-environmental behaviour of students. Within the past decade, several higher education institutes have acknowledged the importance of integrating sustainability into the educational curriculum to have a focused and explicit impact on society. The current study investigated the relationship between environmental moral education and pro-environmental behaviour wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 102 publications
0
26
0
2
Order By: Relevance
“…Cronbach's coefficients (α) were calculated for all scales that fell within the acceptable range. When it comes to university students, gender and age are the most influential variables [86]. Because the literature indicates that these variables significantly impact students' green behavior, we investigated their impact as control variables in this study.…”
Section: Instrumentsmentioning
confidence: 99%
“…Cronbach's coefficients (α) were calculated for all scales that fell within the acceptable range. When it comes to university students, gender and age are the most influential variables [86]. Because the literature indicates that these variables significantly impact students' green behavior, we investigated their impact as control variables in this study.…”
Section: Instrumentsmentioning
confidence: 99%
“…Moral and behavioral consciousness regulates different factors that are instrumental in decision making, which include the environment, existing culture, economic status, and intrinsic motivations [ 28 , 29 ]. Developing moral consciousness among people is instrumental in reviewing personal actions such as the consumption of fossil fuels, which is the largest source of environmental degradation and a major contributor to global warming [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Maarten (2011) suggested that moral beliefs can promote the generation/occurrence of pro-environmental behaviors to a certain degree, such as donating and volunteering [ 34 ]. As a kind of prosocial behavior, moral beliefs also play a certain role in promoting pro-environmental behavior [ 37 ]. However, further in-depth study on their predictive effect and influencing mechanism is needed.…”
Section: Theoretical Basis and Research Hypothesesmentioning
confidence: 99%